PERWALIAN UNTUK PROSES PERALIHAN HAK ATAS TANAH YANG TERJADI KARENA PEWARISAN - , RIFKY ANGGA NOERSAKTI, Nurhadi Darussalam, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Author wrote the final project report with the title \"Trusteeship for Transition Process of Land which Occurs Due to Inheritance\", because author wanted to know what kind of procedure and documents must be completedfor transition when there is an underage children as a heir. In addition to writing the final project report, student is required to perform internship which aims to absorb knowledge from internship. By performing Field internship, author also had an opportunity to get more comprehensive knowledge and learned how to apply the competencies as a diploma internship. By law, parent who still alive become a trustee for underage children. However, if the transfer of the assets happen, the childâs trustee should be appointed through Court Decision. This process must be accomplished so that the parent can act as a trustee in the transfer process of the assets.